Effect of the cover factor on the tensile properties of multi-core flax/polypropylene micro-braided hybrid yarns for thermoplastic biocomposites. Issue 2 (June 2022) - Zhai, Wenqian; Wang, Peng; Soulat, Damien; Legrand, Xavier
With the growing popularity of hybrid yarn techniques, the micro-braided yarn is becoming a good choice as one kind of intermediate materials for thermoplastic biocomposites, by presenting favorable morphology during the preform process and lowering the resin flow distance during the thermo-compression process. In this article, different flax/polypropylene (PP) based multi-core micro-braided hybrid yarns with the similar total number of flax core fibers were manufactured, by varying the parameters: multi-core configuration and braiding angle; both dry-and thermo- states tensile tests on yarns were carried out, since it is necessary to simulate the deforming behavior of a single hybrid yarn during the thermoforming process. The objective is to determine the cover factor especially for multi-core micro-braided yarn as a comprehensive textile indicator; and to study the influence of the cover factor parameters on mechanical tensile properties at the yarn scale. It has been observed that the cover factor parameters contributed the braider effect (friction and compression) on flax cores in the dry-state and lubricant effect (distribution and viscosity) in the thermo-state; further influenced the characterizations. Increasing multi-core configuration and braiding angle can both increase the tensile strength; larger cover factor results in greater tensile stiffness both in dry-and thermo-states.